Integration of Artificial Intelligence in Learning: Challenges, Ethics, and Implications for Teacher Professionalism - Umi Hidayati (PT. AVID MEDIA INDONESIA, 2026)
This study aims to analyze the integration of Artificial Intelligence (AI) in learning by examining implementation challenges, ethical dimensions, and its implications for teacher professionalism in Indonesia. The background of the study is grounded in the acceleration of global and national digital transformation, which has driven the adoption of intelligent technologies in the education sector, yet has not been fully matched by system readiness and human resource capacity. The research employs a qualitative approach with a case study design conducted in secondary schools that have adopted AI in the learning process. Data were collected through in-depth interviews, participant observation, and document analysis, and were subsequently analyzed using thematic analysis. The findings indicate that AI implementation remains partial and largely dependent on teachers’ digital literacy and institutional support. Furthermore, ethical issues such as data protection, algorithmic transparency, and academic integrity emerge as significant challenges. AI integration also encourages a redefinition of teacher professionalism, which now encompasses technopedagogical competence, critical reflection, and moral responsibility in the use of technology. The study concludes that the successful integration of AI in learning requires synergy among adaptive policies, strengthened digital ethics, and continuous professional development for teachers.